Musical Intensity Applied in the Sports and Exercise Domain: An Effective Strategy to Boost Performance? - Van Dyck, Edith (Frontiers in Psychology, 2019)
In the sports and exercise domain, it has been suggested that musical intensity might boost performance. Previous research revealed that pumping up the volume of music might increase running speed, grip strength, and choice reaction time while simultaneously decreasing time to exhaustion and level of perceived exhaustion. However, evidence is still scarce, experimental designs and tested groups vary significantly, and contradicting evidence exists as well. Yet, listening to high-intensity music could be a risky business and exercisers employing such a strategy to improve performance are vulnerable to developing noise-induced hearing problems. Therefore, future research should enquire more profoundly into the inherent boosting qualities of musical intensity and juxtapose experimental results and auditory repercussions in order to uncover possible strategies to combine both in such a way that the exerciser’s health can be safeguarded at all times.